Questioning Implications of the “Sharia Label” on Regulation and Politics of Muslims in Indonesia? Narratives of State Islamic University Students - Bustami Bustami; Helmina Helmina; Kesi Afrilia; Eva Sumanti (Yayasan Abdurrauf Cendekia Nusantara, 2026)
This article discusses the urgency of using the sharia label on Sharia Financial Institution (LKS) products, then what are the consequences of the sharia label being removed, and what are the implications of using the sharia label on the regulation and politics of Muslims in Indonesia. This article aims to question the implications of the “sharia label” on the regulation and politics of Muslims in Indonesia by looking at the narratives of Faculty of Economics and Islamic Business (FEBI) students. This article uses qualitative research methods. Primary data sources come from interviews with several FEBI students from various departments. While secondary data sources are library records including relevant books, scientific articles published in journals and other library materials. Data collection techniques are interviews and documentation. While the data analysis technique used is data condensation, data presentation, and conclusion drawing. The research findings show that the use of halal labels has implications for the overall operation and also the products of Sharia Financial Institutions (LKS) have their own attraction in the mechanism of LKS development. Therefore, through the Sharia Banking Law, the position of the substance of the DSN-MUI fatwa must be stated in the form of Bank Indonesia Regulation (PBI) so that it has binding legal force. Because PBI is one part of the legislation in the National legal system. Therefore, if you look at the understanding of students of the FEBI who are young academics towards the various applications of sharia principles contained in the DSN-MUI Fatwa, it requires a legitimisation process.